Mayaro virus pathogenesis and immunity in rhesus macaques. - Whitney C Weber; Caralyn S Labriola; Craig N Kreklywich; Karina Ray; Nicole N Haese; Takeshi F Andoh; Michael Denton; Samuel Medica; Magdalene M Streblow; Patricia P Smith; Nobuyo Mizuno; Nina Frias; et al. (Public Library of Science (PLoS), 2023)
Mayaro virus (MAYV) is a mosquito-transmitted alphavirus that causes debilitating and persistent arthritogenic disease. While MAYV was previously reported to infect non-human primates (NHP), characterization of MAYV pathogenesis is currently lacking. Therefore, in this study we characterized MAYV infection and immunity in rhesus macaques. To inform the selection of a viral strain for NHP experiments, we evaluated five MAYV strains in C57BL/6 mice and showed that MAYV strain BeAr505411 induced robust tissue dissemination and disease. Three male rhesus macaques were subcutaneously challenged with 105 plaque-forming units of this strain into the arms. Peak plasma viremia occurred at 2 days post-infection (dpi). NHPs were taken to necropsy at 10 dpi to assess viral dissemination, which included the muscles and joints, lymphoid tissues, major organs, male reproductive tissues, as well as peripheral and central nervous system tissues. Histological examination demonstrated that MAYV infection was associated with appendicular joint and muscle inflammation as well as presence of perivascular inflammation in a wide variety of tissues. One animal developed a maculopapular rash and two NHP had viral RNA detected in upper torso skin samples, which was associated with the presence of perivascular and perifollicular lymphocytic aggregation. Analysis of longitudinal peripheral blood samples indicated a robust innate and adaptive immune activation, including the presence of anti-MAYV neutralizing antibodies with activity against related Una virus and chikungunya virus. Inflammatory cytokines and monocyte activation also peaked coincident with viremia, which was well supported by our transcriptomic analysis highlighting enrichment of interferon signaling and other antiviral processes at 2 days post MAYV infection. The rhesus macaque model of MAYV infection recapitulates many of the aspects of human infection and is poised to facilitate the evaluation of novel therapies and vaccines targeting this re-emerging virus.